AMBIGUITY IN AUTOBIGRAPHICAL NARRATIVES IN NIGERIA: VALORIZING SEXISM AND DISPLACEMENT IN OGONI COSMOLOGY - Christopher Babatunde Ogunyemi (English Review: Journal of English Education, 2016)
This paper focuses on the examination of ambiguity in autobiographical writings in Nigeria. It underscores the architectonic discourse, cultural alienation and ‘self-elevation’ in some selected autobiographies. Ambiguity in this instance visualizes that these male narratives hinge on something, which is what we now wish to excavate as an area of serious academic endeavour. And it also hinges on how Saro Wiwa’s autobiographies who happen to be male is inevitably sexist in orientation, this will, however, be shown when examining in particular the structuring (narratological devices) of the texts. This work valorizes the cardinal representations of self and male gender in enhancing identity for people of diverse perspectives without appreciating female voices which constitute an integral part of the literary history and ideologue. ‘Negating women in art is negating history because history is the main discipline through which we can understand gender’ (Brereton, 1998, p. 17). This paper encapsulates the motif of dominance and oppression of women because women were only made to be seen and not heard or even represented in such art. However, this situation is disheartening because while the ‘African feminist accommodates men and make them its central assurance, love and care’ (Chukwuma, 1990, p. 15), men who are fickle minded literary ideologues delight in over projecting self using the instrument of ‘I’ in autobiographies without recourse to women who hold some basis to their existence. This research work entails a close analysis of the question of gender and displacement originating from these autobiographical writings originating from Nigeria and the configuration of the motif of metaphor in male dominated gender in five autobiographical writings in line with narratology and Butler’s Theory of performativity. Keywords: autobiography, ambiguity, narratives, saro wiwa, butler, narratology